The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1479164118782887
|View full text |Cite
|
Sign up to set email alerts
|

How sensitive and specific is continuous-wave Doppler for detecting peripheral arterial disease in people with and without diabetes? A cross-sectional study

Abstract: Background: Continuous-wave Doppler is frequently used for detecting peripheral arterial disease in patients with diabetes; however, there is limited evidence investigating diagnostic accuracy. This study aimed to determine sensitivity and specificity of continuous-wave Doppler for detecting peripheral arterial disease in populations with, and without, diabetes and to investigate the influence of disease severity on sensitivity of continuous-wave Doppler for detecting peripheral arterial disease. Results: Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 17 publications
0
36
0
2
Order By: Relevance
“…Among the studies identified, the most commonly evaluated bedside test was the ABI, which was reported in 13 of the studies. Two studies that did not use ABI were written by authors who previously reported on the use of ABI in a smaller cohort of patients and a further study reported ankle pressure without correcting for brachial pressure . The threshold value for diagnosis of PAD was defined as <0.9 or ≤0.9 in most studies; however, three studies used both a lower and upper threshold for diagnosis (<0.9 or >1.3 and ≤0.9 or ≥1.4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the studies identified, the most commonly evaluated bedside test was the ABI, which was reported in 13 of the studies. Two studies that did not use ABI were written by authors who previously reported on the use of ABI in a smaller cohort of patients and a further study reported ankle pressure without correcting for brachial pressure . The threshold value for diagnosis of PAD was defined as <0.9 or ≤0.9 in most studies; however, three studies used both a lower and upper threshold for diagnosis (<0.9 or >1.3 and ≤0.9 or ≥1.4 .…”
Section: Resultsmentioning
confidence: 99%
“…Systolic toe pressure was reported by two studies (using <97 mm Hg or <50 mm Hg as thresholds). Other tests used included TcPO 2 altered waveforms on colour wave Doppler audible Doppler waveforms, pulse reappearance time (PRT), change in pulse oximetry and pole test . One study looked at a wide variety of subjective clinical examination tests …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic thresholds for ABI were in accordance with current international guidelines, with an ABI < 0.9 considered abnormal . TBI values of <0.6 were considered abnormal, and monophasic CWD were considered abnormal . However, due to the small number of participants with abnormal ABI values (n = 3 in each group), the association between the continuous measure of ABI and gait velocity was assessed using Pearson's r correlation.…”
Section: Methodsmentioning
confidence: 99%